Ethnographically oriented assessment of an emergent multidisciplinary science ESP group project module - Ngoepe, L.J. (South African Journal of Higher Education, 2017)
When language and content lecturers in a multidisciplinary setting assess what they teach in concert, they tend to benefit from that enriching experience but students stand to benefit more. This paper describes some multidisciplinary assessment of an emergent science English for Specific Purposes (ESP) project module. The quintessentially South African module is meant to enhance the performance of English and Study Skills (ESS) ESP under-prepared science students. The project was assessed formatively in concert by students, language - as well as content lecturers. This science ESP course is integrated in a Bachelor of Science Extended Degree Programme (BSc EDP) curriculum at the University of Limpopo (UL). The researcher mainly analysed the performance of the students in the project module over a four year period.